Nintedanib in idiopathic pulmonary fibrosis: practical management recommendations for potential adverse events - Bendstrup, Elisabeth; Wuyts, Wim; Alfaro, Tiago M.; Chaudhuri, Nazia; Cornelissen, Robin; Kreuter, Michael; Melgaard Nielsen, Kirsten; Münster, Anna-Marie B.; Myllärniemi, Marjukka; Ravaglia, Claudia; Vanuytsel, Tim; Wijsenbeek, Marlies (Respiration, 2019)
Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease with a dismal survival rate of only 3 years and no curative pharmacological therapy. The recent approval of 2 anti-fibrotic drugs (nintedanib and pirfenidone) that slow disease progression has provided some hope for patients. However, effectively managing anti-fibrotic treatment can be a challenge due to tolerability issues, the presence of pulmonary and extra-pulmonary comorbidities, and the need for concomitant medications in many patients. In general, making clear evidence-based decisions can be difficult for physicians because patients with comorbidities are often excluded from clinical trials. Since currently anti-fibrotic drugs are the only effective therapeutics capable of slowing disease progression, it is imperative that all treatment options are thoroughly evaluated and exhausted in each individual, irrespective of complicating factors, to permit the best outcome for the patient. In this review, we present data from clinical trials, post hoc analyses, post-marketing surveillance, and real-world studies that are relevant to the management of nintedanib treatment. In addition, we also provide practical recommendations developed by a multidisciplinary panel of experts for the management of nintedanib treatment in patients with IPF associated complications and those experiencing gastrointestinal side effects.
Gesehen am 25.06.2019